PENGARUH KNOWLEDGE SHARING DAN TRANSFER OF TRAININING TERHADAP KINERJA PEGAWAI BALAI WILAYAH SUNGAI SULAWESI IV PROVINSI SULAWESI TENGGARA - Indah Harwaty S; Al Asy Ari Adnan Hakim; Vicki Ardiansyah (Mega Aktiva, 2019)
This study aims to determine the effect of knowledge sharing and transfer of training on the performance of employees of the Sulawesi River Region IV Regional Office in Southeast Sulawesi Province. This research uses a quantitative approach, with the subject of the study being all employees of the Sulawesi River Region IV of the Southeast Sulawesi Province who have attended the training, amounting to 80 respondents. The type of data used is primary data through questionnaire distribution, which is then analyzed using the statistical method of multiple linear regression analysis. Based on the results it was found that knowledge sharing and transfer of training together had a significant positive effect on improving employee performance. This means that any improvement made by employees either through knowledge sharing or transfer of training will also have an impact on improving the performance of the employees of the Sulawesi River Region IV of the Southeast Sulawesi Province.